Design, Fabrication, and Application of GaN-Based Micro-LED Arrays With Individual Addressing by N-Electrodes - Enyuan Xie (IEEE Photonics Journal, 2017)
We demonstrate the development, performance, and application of a GaN-based micro-light emitting diode ( $μ$ LED) array sharing a common p-electrode (anode), and with individually addressable n-electrodes (cathodes). Compared to conventional GaN-based LED arrays, this array design employs a reversed structure of common and individual electrodes, which makes it innovative and compatible with n-type metal-oxide-semiconductor (NMOS) transistor-based drivers for faster modulation. Excellent performance characteristics are illustrated by an example array emitting at 450 nm. At a current density of 17.7 kA/cm $^2$ in direct-current operation, the optical power and small signal electrical-to-optical modulation bandwidth of a single $μ$ LED element with 24 $μ$ m diameter are over 2.0 mW and 440 MHz, respectively. The optimized fabrication process also ensures a high yield of working $μ$ LED elements per array and excellent element-to-element uniformity of electrical/optical characteristics. Results on visible light communication are presented as an application of an array integrated with an NMOS driver. Data transmission at several hundred Mb/s without bit error is achieved for single- and multiple- $μ$ LED-element operations, under an on–off-keying modulation scheme. Transmission of stepped sawtooth waveforms is also demonstrated to confirm that the $μ$ LED elements can transmit discrete multilevel signals.